Pengaruh Prosedur dan Fasilitas Pelayanan Terhadap Kualitas Pelayanan Peserta Program Jamkesmas Di Puskdsmas I Cilongok - Mukhadiono,; Subagyo, Widyo (Jurusan Keperawatan FIKES UNSOED, 2011)
Problems that are often found in public services, including health care, is the quality of service that is not fully satisfactory. This study aims to examinethe influence of service procedures and facilities to service quality of public health. This research used survey method with explanatory type. The target of this research is participant of Jamkesmas Program. Sampling technique used accidental sampling. Research instrument used questionnare. Analyse done quantitatively with product moment correlation and multiple regression. Result of research showed that service procedure and service facility, both of partially and simultantly, has significant influence toward service quality at participant of Jamkesmas Program. It was showed that service procedure and service facility have important role to support service quality. Based from the result, all of hypothesis proposed was accepted.